Becoming a librarian: from Sydney to Hong Kong via a LIS degree. Issue 4 (1st October 2016) - Hare, Joanna
Abstract: This is a personal reflection of a new librarian from Sydney, Australia. It is a reflection on her previous lives before her LIS education, and her preparedness upon entering the workforce. The author relates how she learned and developed in the first two years of her library employment, and how she found herself working in an academic library in Hong Kong. The author also shares the results of a brief survey of new librarians working in academic libraries in Hong Kong regarding their experiences of LIS education and first years in the profession. The article concludes with some recommendations for other new librarians entering the workforce.